Quality education and the Caribbean Single Market and Economy (CSME) in an increasingly competitive and rapidly changing global environment : lecture - Bourne, Compton (CDB [St. Michael]BB, 2008)
Profiles the development situation of the Caribbean and highlights some features of the global environment and the basis for international competitiveness. Looks at how the CSME or regional integration may be expected to better prepare Caribbean economies to compete. Indicates what are some implications for education quality.